Degradation And Stability Of Green Composites Fabricated From Oil Palm Empty Fruit Bunch Fiber And Polylactic Acid: Effect Of Fiber Length - Beg, M. D. H.; Alam, A. K. M. Moshiul; Mina, M. F.; Mamun, A. A.; Bledzki, A. K. (SAGE Publications, 2015)
In this work, polylactic acid and oil palm empty fruit bunch fiber-reinforced green composites have been fabricated by using random and fixed-length fibers through extrusion followed by injection molding. The prepared composites have been characterized by mechanical tests, thermal analysis, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray diffractometry. Among all fabricated composites having various sizes and contents of fibers, 30-mm long and 40 wt% empty fruit bunch fiber-incorporated composites show the optimum tensile strength and modulus. As compared to raw empty fruit bunch fiber-loaded composites, simultaneous ultrasound and alkali-treated empty fruit bunch-reinforced composites have revealed improved mechanical performances, enhanced crystallinity, and thermal stability. In case of soil burial degradation studies, treated empty fruit bunch fiber-reinforced composite has been found to be more stable than untreated fiber-reinforced composite.